Long‐term monitoring of IOX4 in horse hair and its longitudinal distribution with segmental analysis using liquid chromatography/electrospray ionization Q Exactive high‐resolution mass spectrometry for the purpose of doping control. Issue 7 (7th March 2022) - Ishii, Hideaki; Shibuya, Mariko; So, Yat‐Ming; Wong, Jenny K. Y.; Ho, Emmie N. M.; Kusano, Kanichi; Sone, Yu; Kamiya, Takahiro; Wakuno, Ai; Ito, Hideki; Miyata, Kenji; Yamada, Masayuki; et al.
Abstract: IOX4, a hypoxia‐inducible factor stabilizer, is classified as a banned substance for horses in both horse racing and equestrian sports. We recently reported the pharmacokinetic profiles of IOX4 in horse plasma and urine and also identified potential monitoring targets for the doping control purpose. In this study, a long‐term longitudinal analysis of IOX4 in horse hair after a nasoesophageal administration of IOX4 (500 mg/day for 3 days) to three thoroughbred mares is presented for the first time for controlling the abuse/misuse of IOX4. Six bunches of mane hair were collected at 0 (pre), 1, 2, 3, and 6 month(s) postadministration. Our results showed that the presence of IOX4 was identified in all postadministration horse hair samples, but no metabolite could be detected. The detection window for IOX4 could achieve up to 6‐month postadministration (last sampling point) by monitoring IOX4 in hair. In order to evaluate the longitudinal distribution of IOX4 over 6 months, a validated quantification method of IOX4 in hair was developed for the analysis of the postadministration samples. Segmental analysis of 2‐cm cut hair across the entire length of postadministration hair showed that IOX4 could be quantified up to the level of 1.84 pg/mg. In addition, it was found that the movement of the incorporated IOX4 band in the hair shaft over 6 months varied among the three horses due to individual variation and a significant diffusion of IOX4 band up to 10 cm width was also observed in the 6‐month postadministration hair samples. Abstract : IOX4, a hypoxia‐inducible factor stabilizer, was nasoesophagealy administered to three thoroughbred mares. Segmental analysis of postadministration hair samples (collected up to 6 months) was performed to reveal the longitudinal distribution of IOX4 in the hair shaft and to confirm the detectability of IOX4 and its possible metabolites for the doping control purpose. The results showed that only IOX4 was detected in the postadministration samples, and the incorporated IOX4 gradually diffused along the hair shaft over time.